Morphophonemic Allomorphy of the Prefix Um- In Toba Batak: An Extended Generative Morphology Analysis - Esron Ambarita; Edi Suprayetno; Atabong Alemanjoh Mariana Nkea; Emmanuel Kyei (English Lecturers and Teachers Association (ELTA), 2026)
This study investigates the morphophonemic allomorphy of the prefix um- in Toba Batak and evaluates the applicability of an extended generative morphology framework for analyzing Austronesian morphological systems. The data were collected from twelve native speakers residing in Samosir and Toba Samosir Regencies through elicitation, observation, and semi-structured interviews. The study employs an expanded version of generative morphology derived from Halle’s model, incorporating the components List of Morphemes, Word Formation Rules, FILTER, DICTIONARY, Orthographic Rules, and Phonological Rules. This extended framework was designed to accommodate the distinctive morphological and phonological characteristics of Toba Batak, which are insufficiently represented in models originally developed for Indo-European languages. The findings identify four morphophonemic allomorphs of the prefix um-, namely umm-, um-, un-, and uŋ-, each conditioned by systematic phonological environments and morphophonemic processes. The analysis demonstrates that the prefix exhibits high morphological productivity in forming grammatical and lexical meanings through predictable sound alternations. The study contributes to generative morphology by extending Hallean analysis to an underrepresented regional language while also supporting language documentation, revitalization, and preservation efforts for Toba Batak. Furthermore, the research provides empirical evidence that extended generative morphology can effectively explain morphophonemic variation in minority languages, offering a replicable analytical approach for future studies on indigenous languages across Austronesian linguistic communities. Keywords : Morphophonemic allomorphy; Toba Batak language; Generative morphology; Prefix um-; Austronesian linguistics